DIFFERENCES AND SIMILARITIES BETWEEN NUMBER OF NOUN IN ENGLISH AND UZBEK LANGUAGES - Kudratova Mukhlisa; Aziz Mukhamadiev (Лучшие интеллектуальные исследования, 2024)
Annotation: a noun in grammar fundamental part of speech that serves as the name of a person, place, thing, or idea. It provides a way to identify and refer to objects and concepts in language. Nouns can represent both tangible entities, like "dog" or "house," and abstract concepts, such as "happiness" or "freedom." They play a crucial role in constructing sentences and conveying meaning. Nouns can be singular or plural, common or proper, concrete or abstract, and countable or uncountable, depending on their characteristics and usage in a sentence. In English, nouns often function as subjects, objects, or complements in sentences, helping to communicate ideas clearly and effectively. Understanding nouns is essential for mastering language and expressing thoughts and ideas accurately.